Genome-Wide Identification, Characterization, and Expression Profile Analysis of CONSTANS-like Genes in Woodland Strawberry (Fragaria vesca) - Zhao, Xinyong; Yu, Fuhai; Guo, Qing; Wang, Yu; Zhang, Zhihong; Liu, Yuexue (Frontiers in Plant Science, 2022)
CONSTANS-like gene (CO-like) is one of the most important regulators in the flowering process of plant, playing a core role in the photoperiodic flowering induction pathway. In this study, we identified 10 distinct CO-like genes (FveCOs) in the woodland strawberry (F. vesca). They were classified into three groups with specific gene structure characteristics or protein domains in each group. Effect of selection pressure on the FveCOs in woodland strawberry was tested by Ka/Ks and it was shown that the evolution rate of FveCOs was controlled by purification selection factors. Intraspecific synteny analysis of woodland strawberry FveCOs showed that at least 1 duplification event existed in the gene family members. Collinearity analysis of woodland strawberry genome with genomes of Arabidopsis, rice (Oryza sativa) and apple (Malus × domestica) showed that CO-like genes of F.vesca and Malus × domestica owned higher similarity for their similar genomes compared with other two species. The FveCOs showed different tissue-specific expression patterns. Moreover, Real-time quantitative PCR results revealed that expressions of the most FveCOs followed a 24-hour rhythm oscillation in both Long Day (LD) and Short Day (SD) conditions. Further expression analysis showed that the individual expression changing profile of FveCO3 and FveCO5 was opposite to each other in both LD and SD. Moreover, expression of FveCO3 and FveCO5 were both negatively correlated with the flowering time variation of the woodland strawberry grown under LD and SD, indicating their potential vital roles in the photoperiodic flowering regulation. Further protein interaction network analysis also showed that most of the candidate interaction proteins of FveCO3 and FveCO5 were predicted to be the flowering regulators. Finally, LUC assay indicated that both FveCO3 and FveCO5 could bind to the promoter of FveFT1, the key regulator of flowering regulation in woodland strawberry, and thus activate its expression. Taken together, this study laid a foundation for understanding of the exact roles of FveCOs in the reproductive development regulation of woodland strawberry, especially in the photoperiodic flowering process.